ANALISIS KETIDAKLENGKAPAN PENGISIAN BERKAS REKAM MEDIS DI RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA - Solikhah, .; Pamungkas, Tiara Wahyu; Marwati, Triyani (Jurnal Kesehatan Masyarakat (Journal of Public Health), 2010)
Background: The medical records is one important part in helping the implementation of service delivery to patients at the hospital. According Permenkes No. 269/Menkes/Per/III/2008 about medical records, medical records are files that contain records and documents concerning patient identification, examination, treatment, action and other services that have been given to the patient. The main purpose of medical records is as evidence of disease progression and treatment of patients who have been granted, means of communication among the health workers who provide parawatan to the patient, the source of information for research and education, as well as the source of the data collection of health statistics (WHO, 2002). The primary responsibility will be the completeness of medical records lies in the responsible physician treat the patient. In previous studies, there is still a problem in the charging file medical records of inpatients who sometimes can not be filled by a physician. The purpose of this study is to determine the cause of the incompleteness of filling the patients medical record file PKU Muhammadiyah Hospital in Yogyakarta.Methods: This was a non-experimental research qualitative methods. This study used cross-sectional study design. The population in this study is to file medical records. The sample in this study is an incomplete file fill in May 2010. Respondents in this research are specialists, doctors who served in internal medicine ward, and medical records officers. Tested the validity of qualitative data through triangulation techniques.Results: The percentage of incompleteness of medical records file charging Disease Section PKU Muhammadiyah Hospital in Yogyakarta is 40.43%. The cause of the incompleteness of medical records file charging Disease Section is a limitation of time and indiscipline health workers to the completeness of filling medical record file. Conclusions: Completeness of medical record file filling very important to set the course of activities and communication between relevant personnel as the basis of quality of service. The factors that become obstacles to overcome if all the officers realized the importance of completeness of filling the medical record file and run it. Keywords : incompleteness, Causes, Medical Records